Whole-genome sequencing of Listeria monocytogenes isolated from the first listeriosis foodborne outbreak in South Korea - Lee, Seung Hun; Lee, Sangmi; Park, Sang Hun; Koo, Ok Kyung (Frontiers in Microbiology, 2023)
Listeria monocytogenes is a foodborne pathogen that causes listeriosis in humans with severe symptoms. In South Korea, listeriosis had only been reported sporadically among hospitalized patients until the first foodborne outbreak occurred in 2018. In this study, a L. monocytogenes strain responsible for this outbreak (FSCNU0110) was characterized via whole genome sequencing and compared with publicly available L. monocytogenes genomes of the same clonal complex (CC). Strain FSCNU0110 belonged to multilocus sequence typing (MLST)-based sequence type 224 and CC224, and core genome MLST-based sublineage 6178. The strain harbored tetracycline resistance gene tetM, four other antibiotic resistance genes, and 64 virulence genes, including Listeria pathogenicity island 1 (LIPI-1) and LIPI-3. Interestingly, llsX in LIPI-3 exhibited a characteristic SNP (deletion of A in position 4, resulting in a premature stop codon) that was missing among all CC224 strains isolated overseas but was conserved among those from South Korea. In addition, the tetM gene was also detected only in a subset of CC224 strains from South Korea. These findings will provide an essential basis for assessing the characteristics of CC224 strains in South Korea that have shown a potential to cause listeriosis outbreaks.